The association between serum squamous cell carcinoma antigen and recurrence and survival of patients with cervical squamous cell carcinoma: A systematic review and meta-analysis - Chuenkamon Charakorn (2019)
© 2018 The Authors Objective: The aim of this systematic review and meta-analysis was to pool association effects of serum squamous cell carcinoma antigen (SCC-Ag) on recurrence and mortality in mainly squamous cell cervical cancer patients. Methods: MEDLINE and Scopus databases were searched up to June 29, 2016. Studies assessing effects of SCC-Ag on recurrence and death in cervical cancer patients were included. Data extraction was independently performed by two reviewers. A meta-analysis was applied for pooling the effects (i.e., risk ratio (RR), hazard ratio (HR), and unstandardized mean difference (USMD)) of SCC-Ag measured before and after treatment on recurrence and death. Results: A total of 61 studies were included. For pretreatment SCC-Ag and recurrence, the pooled RR, HR, and USMD for high versus low serum SCC-Ag were 2.44(95% CI: 1.91, 3.13), 2.23(95% CI: 2.03, 2.45), −7.7(95% CI: -31.7, 16.4), respectively. The corresponding effects for the posttreatment period were 3.91(95% CI: 2.96, 5.16), 3.14(95% CI: 1.29, 7.65), and 3.2(95% CI: -10.6, 17.0), respectively. In addition, patients with high level of pretreatment serum SCC-Ag were also at a higher risk for death than patients with low serum SCC-Ag with a pooled RR of 3.66(95% CI: 2.24, 5.98), pooled HR of 2.50(95% CI: 1.85, 3.37), and pooled USMD of 7.10(95% CI: 4.26, 9.94). The posttreatment serum SCC-Ag effects also reflected a similar trend. Conclusions: The serum SCC-Ag was consistently associated with recurrence and mortality of newly diagnosed cervical cancer. This marker may be useful in monitoring disease progression in cervical cancer patients. Prospero registration number is: CRD42016044024.